The Impact of Divorce on the Development of Emotional Intelligence in Adolescents - Nabilah Nuraisyah; Nabila Naupal Safitri; Rindu Bunga Kasih; Rizkia Cintamy; Darmawati D (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The emotional development of adolescents affected by their parents’ divorce manifests in inappropriate behaviour, such as a lack of motivation to study, withdrawing from friends, displaying anger, apathy, a lack of self-confidence, and even an identity crisis. This study aims to identify issues relating to the emotional intelligence of adolescents resulting from divorce, as well as methods to improve their quality of life. Using a qualitative descriptive method, data were collected through indepth interviews and observations of the main subjects (NAS) residing in Rokan Hulu Regency, along with other informants. The results of the study indicate that complex divorces make adolescents struggle to control their emotions, tending to behave aggressively, or becoming hardened and indifferent as a self-defence mechanism. Adolescents also lose motivation to study due to emotional pressure and a mismatch of interests. However, external support and Islamic counselling techniques have proven capable of enhancing resilience, making adolescents more independent and resilient.